Unity and Multiplicity in Plato's diairetic method in the Sophist - de Oliveira Santos, Bárbara Helena (Revista Archai, 2021)
By placing diairesis in communion with the dialectic, Plato breaks with the dichotomous-univocal Parmenidean structure; in Fragment 2 of the poem On Nature by Parmenides, the goddess establishes that there are only two routes to the truth, one that is and one that is not. Of these two, Parmenides denies the second, stating that it is impossible to know what is not: for the pre-socratic philosopher to know something is related to what is, therefore, for him, it is impossible to know what is not. So, in Parmenides, there is a split between “being” and “not-being”. Therefore, our objective in this article, is to explore the implications, for the diairesis in Plato's Sophist, of the Parmenidean affirmation that non-being is impossible to know.